Mendeteksi Kucurangan Laporan Keuangan Dengan Menggunakan Fraud Diamond - Muhammad Faisal Arif (Insan Cita Bongaya Research Journal, 2021)
This study examines the topic of detecting financial statement fraud by using fraud diamonds. This study aims to examine the effect of Financial Targets, Financial Stability, External Pressure, Nature of Industry, Effective Monitoring, Change in Auditors, Rationalization and Change of Directors on financial statement fraud. In the research method, this study uses secondary data in the form of financial statements, hypothesis testing using SPSS Software Version 21. The results of this study indicate that Financial Targets and Rationalization affect the financial statement fraud while other variables such as Financial Stability, External Pressure, Natura of Industry, Effective Monitoring, Change in Auditors, and Changes of Directors do not affect financial statement fraud. The implication of this research is to test the instruments used in the diamond fraud theory in detecting financial statement fraud.